ESRA19-0226 Comparing analgesic efficacy of quadratus lumborum block versus fascia iliaca block in patients undergoing total hip replacements. (30th August 2019) - Hashmi, J; Cusack, B; Hughes, L; Singh, V; Srinivasan, K
Abstract : Background and aims: Transmuscular quadratus lumborum (TQL) block has been described as an effective option for post-operative analgesia and we hypothesise that TQL block when compared to fascia iliaca block (FIB) will provide better analgesia and less motor block in the initial 24 hour period in patients undergoing elective hip replacements. Methods: Ethics committee approval was taken and this prospective, semi-blind, randomised controlled trial was conducted in patients undergoing elective total hip replacement surgeries. Patients were randomised to either to group a wherein they received spinal anaesthesia with 3.2 ml 0.5% bupivacaine followed by usg guided FIB with 20 ml 0.25% bupivacaine or to group B wherein they received spinal anaesthesia with 3.2 ml 0.5% bupivacaine followed by usg guided QLB with 20 ml 0.25% bupivacaine. All patients received morphine PCA in post-operative period and were reviewed at 6 hours and 24 hours to assess the pain scores and motor block. The primary outcome measure was 24 hour morphine consumption between the two groups and secondary outcome measure were pain score (VNS) and motor block (Modified Bromage Scale) at 6 and 24 hours. Results: There was no statistical difference in morphine consumption between the 2 groups (P 0.699) or pain scores at 6 hours (P 0.540) and 24 hours (P 0.383) and no difference noted in motor block at 6 hours (P 0.497) and at 24 hours (P 0.773) Conclusions: The result of this study demonstrates that TQL does not provide superior analgesia or less motor block then FIB in patients undergoing elective hip replacement surgery.